Economic analysis of sorghum consortia with forages or with dwarf pigeon pea succeeded by soybean or corn - Pascoaloto, Isabô Melina [UNESP]; Andreotti, Marcelo [UNESP]; da Cruz, Sanderley Simões; Sabbag, Omar Jorge [UNESP]; Borghi, Emerson; Lima, Gilmar Cotrin de [UNESP]; Modesto, Viviane Cristina [UNESP] (FapUNIFESP (SciELO), 2017)
The objective of this work was to determine the most economically viable integrated no-tillage croplivestock system by intercropping sorghum with tropical forages or dwarf pigeon pea, succeeded by soybean or corn, over a two-year period. The experiment was carried out in a randomized complete block design with four replicates. The treatments consisted of forage sorghum intercropped with: 'Marandu' grass; 'Marandu' grass and dwarf pigeon pea; 'Mombaça' grass; 'Mombaça' grass and dwarf pigeon pea; and dwarf pigeon pea and single sorghum, harvested for silage in the first cut and regrowth, succeeded by soybean or corn. The following calculations were made: effective operational cost, total operational costs, gross revenues, operational income, profitability index, equilibrium price, and equilibrium productivity. These variables were determined for individual crops, as well as for the sum of the crops occupying the same area over time. The sorghum consortia with 'Mombaça' grass, with or without dwarf pigeon pea, had 18 and 14% lower productivity and profitability, respectively, than the sorghum consortia with 'Marandu' grass, with or without dwarf pigeon pea. Soybean in succession requires less chemical control of the 'Mombaça' grass than corn in succession.
Keywords: Cajanus cajan; Integrated crop-livestock system; Megathyrsus maximus; No-tillage; Profitability; Urochloa brizantha